RECHARGE FLUX TO OCEAN-RIDGE BLACK SMOKER SYSTEMS: A GEOCHEMICAL ESTIMATE FROM ODP HOLE 504B - Teagle D.A.H.; Bickle M.J.; Alt J.C. (My University, 2003)
We use the Sr-isotopic composition of rock and anhydrite, as a monitor of fluid composition, in DSDP/ODP Hole 504B to calculate the recharge flux to the axial high-temperature hydrothermal circulation. The fluid and rock Sr-isotope profiles are well fit by a tracer transport mass-balance model that approximates fluid-solid exchange by linear kinetics. The calculated time-integrated flux of 1.7+/-0.2x106 kg m-2 is significantly less than the 5x106 kg m-2 calculated from thermal models that assume all magma is intruded into a high-level magma chamber at the base of the sheeted dykes. Our low flux is consistent with the observed thermal structure as recorded by secondary alteration minerals in Hole 504B and the intrusion of magma as lenses distributed through the lower oceanic crust. It leaves open the questions as to how the lower oceanic crust cools and how seawater geochemical budgets balance.
Keywords: OCEAN RIDGE; HYDROTHERMAL; SR ISOTOPES; OCEAN DRILLING PROGRAM; ANHYDRITE